THE EFFECTIVENESS OF LABORATORY STEWARDSHIP PROGRAMS IN OPTIMIZING TEST UTILIZATION AND REDUCING UNNECESSARY TESTING - Belgaith Otman Belgaith Alsefri, Ali Ahmed Ali Alsayed, Ghalib Ali Ahmed Almaqadi, Mohammed Abduh Jaber Alhelaly, Noori Mabred Noori Alsayed; Mousa Mohmad Abdo Alhassni, Abubakr Ali Bilghith Alsohbi, Ahmed Belqasem Nasser Alsolbi, Bahni Mohamaad Ibrahim Algoozy, Safiah Hassan Alasiri (Chelonian Research Foundation, 2022)
The proper use of clinical laboratory services is crucial for patient care and necessitates institutional governance. Clinical laboratory stewardship initiatives aim to enhance the process of requesting, obtaining, and understanding suitable laboratory testing. Furthermore, these initiatives prioritize the development, upkeep, and enhancement of systems that provide adequate financial coverage for essential medical tests. Clinical laboratory stewardship initiatives have a positive impact on patient care quality and cost reduction for patients, hospitals, and health systems. This publication, authored by a newly formed multiinstitutional group focused on encouraging and formalizing laboratory stewardship, outlines the essential components of effective hospital-based clinical laboratory stewardship initiatives. The fundamental components will also be beneficial for autonomous commercial clinical labs. Keywords: laboratory stewardship programs, clinical laboratory, testing, commercial clinical labs.